BMT dan Demokratisasi Ekonomi: Membumikan Ekonomi Syari’ah Di Indonesia - Lukman Al-Hakim (Ulumuna, 2009)
In Indonesia, the Islamic economic system has been popular recently since the Bank Muamalah Indonesia was founded and followed by establishment of other shariah financial institutions and businesses such as Bayt al-Mâl wa al-Tamwîl (BMT). BMT, a micro shariah economic institution, is a choice in community based economic development. BMT is significant because the wheel of Indonesian economy is moved by communities from up to down. Populist economy means muslim community”s economy because the majority of Indonesians is muslim and most of them move in the down economy line. It can be said that the improvement of muslim community”s economy shows the improvement of people”s. Conversely, the decline of muslim community”s economy points out the decline of people”s. Therefore, the BMT establishment is a must to build muslim community economic forces in moving the development”s wheel. The BMT development should be designed to support the economic democratization process in Indonesia.